2019
DOI: 10.1111/hae.13762
|View full text |Cite
|
Sign up to set email alerts
|

The changing face of immune tolerance induction in haemophilia A with the advent of emicizumab

Abstract: IntroductionAs a result of the new treatment paradigm that the haemophilia community will face with the availability of novel (non‐factor) therapies, an updated consensus on ITI recommendations and inhibitor management strategies is needed.AimThe Future of Immunotolerance Treatment (FIT) group was established to contemplate, determine and recommend the best management options for patients with haemophilia A and inhibitors.Discussion and ConclusionsDespite the considerable success of emicizumab in the managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
144
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(152 citation statements)
references
References 36 publications
6
144
0
2
Order By: Relevance
“…Moreover, patients <8 years old and a time interval of <5 years between inhibitor detection and the start of ITI have been shown to be positive predictors of successful ITI . Thus, ITI remains an important strategy for inhibitor eradication and restoring the therapeutic benefit of fVIII for bleeds in patients with inhibitors …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients <8 years old and a time interval of <5 years between inhibitor detection and the start of ITI have been shown to be positive predictors of successful ITI . Thus, ITI remains an important strategy for inhibitor eradication and restoring the therapeutic benefit of fVIII for bleeds in patients with inhibitors …”
Section: Discussionmentioning
confidence: 99%
“…In the last several years, novel therapeutics have been evaluated in clinical trials, among which the bispecific monoclonal antibody, emicizumab, has been licensed for the prevention of bleeding in children and adults with haemophilia with and without inhibitors. Recent studies indicate emicizumab is safe and effective for prophylaxis in infants with haemophilia A 15,16 and in immune tolerance induction (ITI) in inhibitor patients, 16,17 and, while costly, is cost-effective in those with inhibitors. 13,14 Whether bleed frequency and bleed severity, long-term joint health and quality of life are comparable to that achieved with factor VIII, therefore, remains unknown.…”
mentioning
confidence: 99%
“…13,14 Whether bleed frequency and bleed severity, long-term joint health and quality of life are comparable to that achieved with factor VIII, therefore, remains unknown. Recent studies indicate emicizumab is safe and effective for prophylaxis in infants with haemophilia A 15,16 and in immune tolerance induction (ITI) in inhibitor patients, 16,17 and, while costly, is cost-effective in those with inhibitors. 18 Yet, there is limited experience with emicizumab in breakthrough bleeding rates and surgical hemostasis in those with and without inhibitors.…”
mentioning
confidence: 99%
“…These early data suggested that ITI can be performed accompanied with emicizumab prophylaxis without safety concerns. In this context, Carcao et al 43 from the Future of Immunotolerance Treatment (FIT) Study Group discussed ITI in the modern era of nonfactor therapies. They proposed starting FVIII at a low dose (50 IU/kg) and low frequency (3 times weekly) escalating to 200 IU/kg daily if the inhibitor titer rises.…”
Section: Questions For the Wider Use Of Emicizumab In The Postmarketimentioning
confidence: 99%
“…Nevertheless, given the limited information and experience in this field, it is difficult to define precise maintenance treatment. The FIT study group recommended continued regular infusions of FVIII once or twice a week for at least 6 months after ITI success 43 . Furthermore, emicizumab alone may be an option, considering the marked reduction in ABR, the burden of frequent FVIII infusions, and catheter‐related thrombotic and infection risks.…”
Section: Questions For the Wider Use Of Emicizumab In The Postmarketimentioning
confidence: 99%